2023
DOI: 10.3390/molecules28041896
|View full text |Cite
|
Sign up to set email alerts
|

Rhombohedral Boron Monosulfide as a p-Type Semiconductor

Abstract: Two-dimensional materials have wide ranging applications in electronic devices and catalysts owing to their unique properties. Boron-based compounds, which exhibit a polymorphic nature, are an attractive choice for developing boron-based two-dimensional materials. Among them, rhombohedral boron monosulfide (r-BS) has recently attracted considerable attention owing to its unique layered structure similar to that of transition metal dichalcogenides and a layer-dependent bandgap. However, experimental evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Finally, we briefly discuss the carrier-doping for r-BS. The previous experimental measurements reported that the synthesized r-BS shows the p-type character. , Thus, to consider the catalytic mechanism of r-BS, we considered the flat band potential E FB of r-BS. This is because the space charge layer owing to the band-bending is an important kinetic descriptor to obtain high-performance OER electrocatalysts with the semiconductor electrode …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we briefly discuss the carrier-doping for r-BS. The previous experimental measurements reported that the synthesized r-BS shows the p-type character. , Thus, to consider the catalytic mechanism of r-BS, we considered the flat band potential E FB of r-BS. This is because the space charge layer owing to the band-bending is an important kinetic descriptor to obtain high-performance OER electrocatalysts with the semiconductor electrode …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the graphene nanoplate in r-BS + G only plays a role in the conductive assistant, and active sites of the r-BS + G catalyst are considered to be located at the basal surface. Furthermore, several experimental measurements of r-BS synthesized under high temperatures and pressures indicates the p-type semiconductor character, , which implies the synthesized r-BS contains some defects. The possibility of surface defects promoting the ORR activity is pointed out by the previous experimental and theoretical studies for the other materials. Therefore, we modeled the r-BS electrode surface by the basal surface using the repeated 4 × 4 slab model with and without the surface defects, as shown in Figure a,b.…”
Section: Computational Detailsmentioning
confidence: 98%
See 1 more Smart Citation